LA CONSTRUCTION DE L’ETHOS POLITIQUE DU PRÉSIDENT BIYA DANS SES DISCOURS À LA JEUNESSE CAMEROUNAISE / THE CONSTRUCTION OF POLITICAL ETHOS IN PRESIDENT PAUL BIYA’S SPEECHES DELIVERED FOR THE YOUTH IN CAMEROON / CONSTRUCŢIA ETOSULUI POLITIC ȊN DISCURSURILE PREŞEDINTELUI BIYA CĂTRE TINERETUL CAMERUNEZ - Nzessé Ladislas; Nguemo Tsagho Carelle (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2017)
This work aims at showing how President Paul Biya constructs self image (ethos) in his speeches to cameroonian youth. Analysing the relationship between prediscursive and discursive ethos of president Biya, is to put into perspective his discursive and social identity respectively. For an effectiveness project of persuasion, the political operator achieves a work either or favourable features reinforcement, or of deconstruction of the negative representations for both specifics identity and self image. This ethos consists of three major figures namely: credibility ethos, identification ethos and paternalist ethos.